Balanced Nutritious Staple Foods as Spesific Intervensions for Stunting Children - Nugroho, Muhammad Ridho; Armeidi, Erwin; Humsi, Firgus (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2023)
Efforts to reduce stunting require nutrition interventions that are carried out in an integrated and integrated manner, including specific and sensitive nutrition interventions. Specific interventions include providing balanced nutritional staple food to stunting toddlers. The sample in this study were 30 stunted toddlers in the Simpang Periuk Health Center working area with the type of intervention, namely providing balanced nutritional staple food for 90 days. The method used in this study uses an experimental design with a pre and post-test approach without control. The statistical test used was the paired sample test by comparing the nutritional status of toddlers before and after intervention. This research was completed in December 2022. The results showed a p-value of 0.000 (<.05), indicating that there was a significant difference in toddler height before and after the intervention was given, so it can also be concluded that the provision of balanced nutritious staple food interventions for 90 days can increase the height of toddlers thereby reducing the stunting rate in the target toddlers.